Perilaku Balok Beton Bertulang Dengan Variasi Tinggi Lubang (Web Opening) Akibat Beban Lentur - Noorhidana, Vera Agustriana (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
The purpose of this study is to analyze the effect of the height of web openings on behaviour ofreinforced concrete beams. The dimensions of web openings are 180mm in length with variationsof height (40mm, 90mm, and 135mm), which is is located on the middle of beam’s span. Thespecimens were four reinforced concrete beams (150mmx270mmx3000mm), namely BP (a beamwithout web openings, BL1 ( a beam with web openings having heights of 40mm), BL2 ( a beamwith web openings having heights of 90mm), and BL3 ( a beam with web openings having heightsof 135mm). There were strengthening bars around the openings to avoid the happening of firstcracks around the openings. Compressive strength of concrete was 20 MPa. The testing of beamsused third-point-loading method which had 2700mm clear span. The results were, the maximumloads of BP, BL1, BL2, and BL3 were 3717kg, 3581kg, dan 3649kg respectively. The curve ofload-deflection and moment-curvature of each beam were sharper from BP, BL1, BL2, and BL3respectively. The conclusion is, the higher of openings will result the higher of maximum loads ofbeams, which is caused by the position of strengthening bars closer to flexural bars resulting thehigher of nominal moments.